Review: Perbedaan Kadar Hemoglobin Menggunakan Hematologi Analyzer dan Spektrofotometer pada Ibu Hamil - Andyanita Hanif Hermawati; Eka Puspitasari; Deny Yusnia Milasari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Hemoglobin is the main component of red blood cells, a conjugated protein that functions to transport oxygen and carbon dioxide. Hemoglobin examination can be done using a hematology analyzer and spectrophotometry. This study aims to determine the data analysis whether there is a difference in hemoglobin levels using a hematology analyzer and spectrophotometry in pregnant women. The method used is Literature Review; the nature of this research is descriptive. The population of this research is health journals that have been through screening, namely journals of differences in hemoglobin levels using a hematology analyzer and spectrophotometry in pregnant women. In this study, the data used are secondary data and data analysis using qualitative data. The results of the evaluation of the study by the Literature Review with hemoglobin levels in pregnant women at Hermina Hospital, Surakarta, showed that the average hemoglobin level of 30 samples of pregnant women using a hematology analyzer was below normal, namely 10.3 gr/dL and normal hemoglobin level is 12.80 gr/dL. The hemoglobin level using spectrophotometry and hematology analyzer on the sample was immediately checked, the results of the hemoglobin levels were 12.98 gr/dL and 11.70 g/dL, respectively. The hemoglobin level showed that the average hemoglobin before being given Fe-Folate with orange water was 11.71 g/dL. The conclusion of this study is the difference in hemoglobin levels is not much different, so there is no difference between the spectrophotometry and the hematology analyzer